Acute non-rheumatic myocarditis following group G streptococcal pharyngitis: a rare mimic of acute myocardial ischemia in a young adult - Elizabeth R. Rimsky; Kaiyu Jia; Aysan Sattarzadeh; Jeffrey Loeffler; Yisroel Grabie; Jonathan Spagnola (European Journal of Case Reports in Internal Medicine)
Background: Acute myocarditis is a rare but serious inflammatory condition of the myocardium, often triggered by infections or rheumatic heart disease. While group A Streptococcus is commonly associated with bacterial myocarditis, group G Streptococcus is rarely implicated. This case highlights a rare instance of non-rheumatic acute myocarditis also known as Streptococcal pharyngitis acute myocarditis caused by group G Streptococcus in a 19-year-old male without rheumatic fever. Case report: A previously healthy 19-year-old male presented with chest pain, fever, and sore throat, prompting hospitalization. The diagnosis of acute myocarditis was based on elevated cardiac biomarkers, electrocardiographic abnormalities, and cardiac magnetic resonance imaging, with group G Streptococcus infection confirmed by throat polymerase chain reaction. The patient responded well to antibiotics and anti-inflammatory therapy. Conclusions: This case highlights group G Streptococcus-induced pharyngitis acute myocarditis, stressing the need for prompt diagnosis and treatment in young adults presenting with recent streptococcal pharyngitis.